2014
DOI: 10.1080/15538362.2013.819182
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Yield of ‘Chok Anan’ (MA 224) Mango with Potassium Nitrate Foliar Sprays

Abstract: Unsynchronized flowering behavior and low fruit set are phenomenon that resulted in low production of mango fruit. The effects of a chemical inducing substance, potassium nitrate (KNO3), on enhancement of flowering on the mango clone 'Chok Anan' (MA 224) and, ultimately, the fruit production were studied. Initially, 12-month-old and 5-year-old mango trees were sprayed with 1%, 2%, and 5% KNO3. The 5-year-old mango trees showed earlier flowering and higher fruit set with 2% KNO3 followed by 5% and 1% KNO3. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In earlier study Saha et al, (2017) reported the highest percent (74.01) of flowering shoot was observed with K 2 HPO 4 1.5 % and KNO 3 1%. These findings are in conformity with Garcia et al, (2008), Sudha et al, (2012), Sarker and Rahim (2013), Afiqah et al, (2014), Maloba et al, (2017) and several others in mango fruit.…”
Section: Effect Of Chemicals On Duration Of Flowering and Percentage Of Flowering Shootssupporting
confidence: 93%
“…In earlier study Saha et al, (2017) reported the highest percent (74.01) of flowering shoot was observed with K 2 HPO 4 1.5 % and KNO 3 1%. These findings are in conformity with Garcia et al, (2008), Sudha et al, (2012), Sarker and Rahim (2013), Afiqah et al, (2014), Maloba et al, (2017) and several others in mango fruit.…”
Section: Effect Of Chemicals On Duration Of Flowering and Percentage Of Flowering Shootssupporting
confidence: 93%
“…It has been reported that the flowering of mango is mediated by high levels of ethylene [64]. Lauchli et al [65] and Afiqah et al [66] explained that KNO 3 could transform the shoots from their vegetative phase (dormant terminal bud) to their reproductive phase, from which they then grow in panicles and finally bear flowers. Generally, all treatments with KNO 3 and putrescine improved fruit set, fruit retention, and number of fruits per tree.…”
Section: Discussionmentioning
confidence: 99%
“…Amrapali (Sarker and Rahim, 2013). Moreover, foliar application of potassium nitrate stimulates flowering in sufficiently mature stems (Afiqah et al, 2014). A more recent research work found that PN at 4 % significantly shortened flowering time by 39 and 36 days on cv.…”
Section: Introductionmentioning
confidence: 97%